'Unintended Cities' and Inoperative Violence. Housing Resistance in Yangon. (26th May 2020) - Astolfo, Giovanna; Boano, Camillo
ABSTRACT: Urban development and city expansion in Yangon, Myanmar happened through the forced resettlement of people from the city toward the periphery. Forced resettlement has become the main mode of urban production since the British colonisation, and is sustained by laws, orders and policies. Building on Benjamin's and Agamben's essays on violence, we claim that it is possible to interrupt the endless cycle of law and violence by locating violence outside the debate around 'means and ends'. Stemming from the authors' experience and repeated encounters with practices of social mobilisation of women in Yangon over the last five years, we have traced the potential for deactivating the 'signature' of violence in the everyday practices of resistance of urban dwellers in the township of HlaingTharYar in Yangon. Through the incremental occupation, trespassing and building up of peripheral 'vacant' land, organised women's groups are challenging the spatial order established by post/colonial regimes.